A conducive environment? The role of need support in the higher education workplace and its effect on academics' experiences of research assessment in the UK. (21st May 2020) - Weinstein, Netta; Chubb, Jennifer A.; Haddock, Geoffrey; Wilsdon, James R.
Abstract: Little is known about how researchers in higher education institutions (HEIs) experience and respond to support received from their departments. The present study investigated how support for researchers' autonomy (choice and self‐expression), relatedness (through connections with colleagues) and competence (feeling effective in one's work) influenced their attitudes towards an external assessment of research. To do so, we surveyed 598 academics from four HEIs in the UK about their attitudes towards one such external assessment: the Research Excellence Framework (REF), a nationwide assessment of research quality and the subject of debate about research evaluation. Our findings, drawing on self‐determination theory, show that departments can shape responses to the REF: individuals whose psychological needs were supported by their academic departments held more positive, and less negative, attitudes towards the REF. This occurred both directly and indirectly through researchers' recognition that the REF had a more positive influence on their research activities and outputs. Abstrakt: Wir wissen wenig darüber, wie Hochschul‐ForscherInnen auf Unterstützung ihrer Instituten reagieren und diese erleben. Die vorliegende Studie untersuchte, wie die Unsterstützung von Autonomie (Wahlfreiheit und Selbstausdruck), Bezogenheit (durch Verbindungen mit KollegInnen), und Kompetenz (sich effektiv in der eigenen Arbeit erleben) die Einstellungen von ForscherInnen zu externer Forschungsbewertung beeinflusst. Zu diesem Zweck befragten wir 598 AkademikerInnen an vier britischen Hochschulen zu ihren Einstellungen gegenüber einer externen Forschungsbewertung: dem Research Excellence Framework (REF), eine landesweite Bewertung von Forschungsqualität, die in der Debatte steht. Beruhend auf der Selbstbestimmungstheorie, zeigen unsere Ergebnisse, dass Institute Reaktionen auf das REF beeinflussen können: Individuen, deren psychologische Bedürfnisse von ihren Instituten unerstützt wurden, hatten mehr positive und weniger negative Einstellungen gegenüber dem REF. Dieser Effekt wurde sowohl direkt wie indirekt dadurch vermittelt, dass ForscherInnen anerkannten, dass das REF einen positiveren Einfluss auf ihre Forschungstätigkeiten und Ergebnisse hatte.